THE EFFECT OF LEVERAGE AND OPERATING CASH FLOW ON EARNINGS PERSISTENCE - Andoko Andoko; Evelyn Natasha William (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
The purpose of this study is to examine the influence of leverage and operating cash flow on earnings persistence. The sample consists of industrial sector companies listed on the Indonesia Stock Exchange, obtained from the LSEG (Refinitiv Eikon) database for the 2021-2024 period using a purposive sampling method, resulting in 332 firm-year observations. The analysis employs ordinary least squares (OLS) regression model using Stata version 16 and SPSS version 27. Descriptive statistics, correlation analysis, classical assumption tests, model specification tests, and hypothesis testing were conducted. Four control variables were included in the model, namely firm size, profitability, sales growth, and capital intensity. The results show that operating cash flow has a significant positive effect on earnings persistence, while leverage has no significant effect. These findings indicate that earnings persistence among industrial sector firms is more strongly driven by operational factors than by financing decisions, suggesting that future research should consider additional variables to obtain a more comprehensive understanding of earnings persistence.